PENGARUH BUDAYA ORGANISASI, KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA KARYAWAN DAN KEPUASAN KERJA DIMEDIASI OLEH MOTIVASI KERJA - Wini Nursolihat; Ferryal Abadi (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Employee performance that always results in progress in achieving organizational goals is very important. The view of the important role of employee performance is a big challenge for company leaders to design various strategies to improve their performance. Several things also affect employee performance, such as how the role of transformational leadership and the suitability of organizational cultural values ​​that can be received by employees can influence factors in employees such as motivation and job satisfaction so as to improve performance. Therefore, the purpose of this research is to know the role of transformational leadership, organizational culture, motivation, job satisfaction on performance. The study was conducted in February-March 2022 with a survey using a questionnaire to 200 permanent employees in a wall paint manufacturing company. Analysis of this research data using SEM. The conclusion of the research shows that transformational leadership and organizational culture each have an influence on motivation, transformational leadership and job satisfaction each have an influence on employee performance, motivation has an influence on job satisfaction. Furthermore, the mediating results found that motivation can mediate the relationship between transformational leadership on job satisfaction, motivation can mediate the relationship between organizational culture on job satisfaction and job satisfaction can mediate the relationship between motivation and performance. However, it was found that transformational leadership and organizational culture had no effect on job satisfaction, then organizational culture had no effect on employee performance.